Role and mechanism of CD90+ fibroblasts in inflammatory diseases and malignant tumors - Zeng, Feng; Gao, Mengxiang; Liao, Shan; Zhou, Zihua; Luo, Gengqiu; Zhou, Yanhong (Molecular medicine (Cambridge, Mass.), 2023)
Fibroblasts are highly heterogeneous mesenchymal stromal cells, and different fibroblast subpopulations play different roles. A subpopulation of fibroblasts expressing CD90, a 25–37 kDa glycosylphosphatidylinositol anchored protein, plays a dominant role in the fibrotic and pro-inflammatory state. In this review, we focused on CD90 + fibroblasts, and their roles and possible mechanisms in disease processes. First, the main biological functions of CD90 + fibroblasts in inducing angiogenesis and maintaining tissue homeostasis are described. Second, the role and possible mechanism of CD90 + fibroblasts in inducing pulmonary fibrosis, inflammatory arthritis, inflammatory skin diseases, and scar formation are introduced, and we discuss how CD90 + cancer-associated fibroblasts might serve as promising cancer biomarkers. Finally, we propose future research directions related to CD90 + fibroblasts. This review will provide a theoretical basis for the diagnosis and treatment CD90 + fibroblast-related disease.